Ultrasonic-assisted green synthesis of flower like silver nanocolloids using marine sponge extract and its effect on oral biofilm bacteria and oral cancer cell lines. (October 2016) - Inbakandan, D.; Kumar, C.; Bavanilatha, M.; Ravindra, Dune Naga; Kirubagaran, R.; Khan, S. Ajmal
Abstract: The knowhow followed for synthesis, characterization and application of nanomaterials has become an important branch of nanoscience. The use of marine sponges for the synthesis of metal nanoparticles is still in the budding level of current nanobiotechnology. This paper reports a single step one pot biosynthesis utilizing marine sponge ( Haliclona exigua ) extract as a reducing agent by means of a conventional ultrasonic bath on the formation and growth of flower like silver nanocolloids. These silver nanocolloids were characterized through UV visible spectroscopy, High Resolution Transmission Electron Microscope, Fourier Transform Infrared spectroscopy and X-ray Diffractometer. Further, antibacterial activity and antiproliferative activity were done against oral biofilm bacteria and oral cancer cell lines for the biosynthesized flower like silver nanocolloids. Water soluble organic amines were responsible for the syntheses of nanomaterials which have a size range from 100 to 120 nm. An average size of 9.1 mm zone of inhibition was recorded with 10.0 μg of silver nanocolloids against oral biofilm bacteria. The estimated half maximal inhibitory concentration value for flower like silver nanocolloids was 0.6 μg/ml for oral cancer cell lines. Highlights: Single step one pot ultrasonic-assisted green synthesis of silver nanocolloids. Utilization of Marine bioresources ( Haliclona exigua ) for synthesis of nanocolloids. Silver nanocolloids as a promising drug for oral care and dental health. Significant antibacterial activity against oral biofilms. Significant antiproliferative effect on human oral cancer KB cell line.